TINJAUAN YURIDIS HAK TANGGUNGAN DALAM PENDAFTARAN TANAH DI INDONESIA: REGULASI DAN PRAKTIK DI LAPANGAN - Rokhmad, Firman Nur; Ningsih, Dita Cahya; Chairunnisa, Nursyifa; Niravita, Aprila; Fikri, Muhammad Adymas Hikal (Universitas Kapuas, 2025)
Mortgage rights are security rights imposed on land rights with the aim of providing legal certainty and priority status for the owner. Regulations and practices in the field must go hand in hand in accordance with the initial objectives. This study aims to comprehensively analyze the legal aspects of mortgage rights, including strengths, weaknesses, and opportunities and challenges faced in the implementation of land mortgage registration in Indonesia. The type of research used is normative legal with a qualitative descriptive approach. This study found that in terms of regulations, land mortgage rights have been regulated properly and maturely. However, in practice in the field, the mortgage registration process is still marked by various obstacles, both in terms of procedures, costs, and public understanding. Therefore, the government needs to consider improving the mortgage recording and reporting system, including the use of technology that supports data transparency and accuracy, such as a nationally integrated digital system.